Editorial - Neves, Pedro Soares (BBDS - Black Book: Drawing and Sketching, 2023)
Political intentions – drawing and it’s social and political dimensions This is a call for papers that explore the social and political content in drawing. This can focus on the field of graphic art including posters, graffiti, murals and comics. It can also be about social and political content in fine art and independent practice. The aim of the issue it to see, through written and pictorial submissions, how drawing is and has been used as a way of documenting, promoting, and exploring social and political issues and themes. We accept image-based submissions with supporting text.